Root growth and distribution in sugarcane cultivars fertigated by a subsurface drip system - Ohashi,Augusto Yukitaka Pessinatti (2015)
Despite of the agronomic importance for water management, few studies of sugarcane roots have been performed under field conditions during the crop cycle. The aim of this study was to determine the cumulative root density (LA), root distribution on soil profile and the effective rooting depth (ERD) for three sugarcane cultivars using the minirhizotron method. A field experiment was done with sugarcane cultivars IACSP94-2094, IACSP94-2101 and SP79-1011 grown under subsurface drip fertigation. Soil chemical and physical characteristics were also evaluated. Root evaluations were taken at 38, 58, 123, 185 and 205 days during the second ratoon, considering the soil profile until 0.8 m depth. The highest LA and root growth rates were found up to 0.4 m soil layer for all cultivars. Root growth rate varied during the crop cycle, with the highest values being found between 38 and 58 days after ratoon (DAR). There was a genotypic variation in root growth, with IACSP94-2101 showing the highest LA of 12.9 mm cm–2. The total root length observed around the tube (0.16892 m2) was 10.8, 5.9 and 2.5 m up to 0.8 m depth for IACSP94-2101, SP79-1011 and IACSP94-2094, respectively at 205 DAR. The effective rooting depth varied during the cycle for IACSP94-2094, but all cultivars presented an effective depth of 0.4 m at 205 DAR.